Scalar-bipolar asymptotic modules for solving (2+1)-dimensional nonlinear evolution equations with constraints - Jaulent, Marcel; Manna, Miguel A. [UNESP]; Alonso, Luis Martinez (Elsevier B.V., 1988)
An infinite hierarchy of solvable systems of purely differential nonlinear equations is introduced within the framework of asymptotic modules. Eacy system consists of (2+1)-dimensional evolution equations for two complex functions and of quite strong differential constraints. It may be interpreted formally as an integro-differential equation in (1+1) dimensions. © 1988.